Efficacy of i-Scan Imaging for the Detection and Diagnosis of Early Gastric Carcinomas - Junichi Nishimura; Jun Nishikawa; Munetaka Nakamura; Atsushi Goto; Kouichi Hamabe; Shinichi Hashimoto; Takeshi Okamoto; Masato Suenaga; Yusuke Fujita; Yoshihiko Hamamoto; Isao Sakaida (Gastroenterology Research and Practice)
We determined comparative efficacy of i-Scan for detection and diagnosis of gastric cancer. Ten patients diagnosed with early gastric cancer based on histopathological findings were analyzed. White light and i-Scan moving images recorded from these patients in twin mode were separated into white light and i-Scan. Twelve endoscopists (three different skill levels) blinded to patient information evaluated the images. Correlation between demarcation accuracy and lesion brightness on still images was investigated. No significant differences were found in diagnostic accuracy between white light and i-Scan moving images for tumor detection rate (91.7% versus 90.8%, P=0.777). Diagnostic accuracy of tumor size was comparable between novice and experienced endoscopists for i-Scan moving images (65.7% versus 71.1%, P=0.528), whereas it was significantly lower for white light moving images (41.2% versus 79.5%, P=0.019). Tumor demarcation accuracy was significantly better with white light than i-Scan still images (71.0% versus 65.8%, P=0.033). Correlations between demarcation accuracy and brightness reached highs of 0.75 for white light and 0.89 for i-Scan imaging. Efficacy of i-Scan over that of white light imaging for detecting and diagnosing gastric cancer was not shown; however, the diagnostic capability of i-Scan can be improved if imaging conditions are optimized.